Rapid determination of sodium pentachlorophenate in bamboo and wooden cutting boards via ultrasonic-assisted liquid-liquid extraction coupled with ultra-performance liquid chromatography-high resolution mass spectrometry - Ye Wang; Mingyou Hu; Fang Wang; Juan Yu; Guojian Shao (PLoS ONE, 2025)
Sodium pentachlorophenate (PCP-Na) is a toxic preservative used in wood products, posing potential health risks through food contact materials. A rapid analytical method combining ultrasonic-assisted liquid-liquid extraction with ultra-performance liquid chromatography-high resolution mass spectrometry (UA-LLE-UPLC-HRMS) was developed for the determination of PCP-Na residues in bamboo and wooden cutting boards. Sample pretreatment involved ultrasonic extraction using methanol/water (50:50 v/v, 2.0% ammonia), followed by liquid-liquid purification with n-hexane/ethyl acetate (60:40 v/v). After solvent evaporation under nitrogen, the residue was reconstituted in the initial mobile phase. Chromatographic separation was achieved on an Acquity UPLC BEH C18 column (2.1 mm × 100 mm, 1.7 µm) using a gradient elution of methanol and 0.01% ammoniated aqueous solution. Detection was performed in negative electrospray ionization (ESI-) mode with targeted single ion monitoring (Targeted-SIM) scanning, utilizing pentachlorophenol-13C6 (PCP-13C6) as an isotopically labeled internal standard. The method exhibited excellent linearity across a concentration range of 1.0–500.0 μg/L (R2 ≥ 0.999), with a limit of detection (LOD) of 0.5 μg/kg and a limit of quantification (LOQ) of 1.5 μg/kg. Validation studies at three spiking levels (20.0, 200.0, and 400.0 μg/kg) demonstrated satisfactory recoveries of 97.2%–99.7% and precision with relative standard deviations (RSDs) of 0.8%–1.7% (n = 6). The total chromatographic runtime was optimized to 6 minutes. Application of this method to Seventy-five commercial cutting boards revealed PCP-Na residues in five samples, with concentrations ranging from 1.3 to 416 mg/kg. This approach features streamlined sample preparation, high sensitivity, robust accuracy, and rapid analysis, making it particularly suitable for routine monitoring of PCP-Na residues in bamboo and wooden food contact materials.